Covid-19 and Communication Barriers: Assessing the Internal Communication in The Field of Health and Safety in The Time of Pandemic - Sebastian KUBASIŃSKI; Joanna SADŁOWSKA-WRZESIŃSKA (Communications of International Proceedings, 2022)
In-organization communication is one of the key elements of efficiently functioning life of a company. An adequate communicating and a transfer of information is the cornerstone of cooperation in every field and on every level of company management. The current research (in the last decade) in the USA, Canada and the UK demonstrates the relation between an internal communication and employee involvement performance. According to them, internal communication is linked to employee attitudes. Conducted studies indicate the existence of dependence concerning satisfaction and internal communication between supervisors and subordinates, and a general attitude at work. There are communication barriers that can impose various unanticipated results, often having the influence over the employee safety. In the scope of this article, it is emphasized that the essence of in-company communication, which, according to the authors of an article, has a real impact on the level of labour environment. It enables to show problems in the field of communication inside the organization and their initial assessment. Simultaneously, the trial assessment of internal communication in a particular company on the basis of current research in this field is carried out by the authors of this article.
Keywords: Covid-19; communication barriers; occupational health and safety.